Thermoplastic resin composition for optical forming body and application thereof
By introducing a thermoplastic resin composition with specific compound structural units, the problem of excessive increase in the glass transition temperature of polycarbonate resin when increasing the refractive index is solved, and the effects of high refractive index, moderate glass transition temperature and high hydrophobicity are achieved, and it is suitable for optical lenses and optical films.
Patent Information
- Application Number
- CN202510002859.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-04-11
AI Technical Summary
While increasing the refractive index, the glass transition temperature is excessively increased, limiting its application in optical systems.
By introducing specific compound structural units, a thermoplastic resin composition is prepared, which contains compound structural units of general formula (A), general formula (B) and general formula (C), and reacts by transesterification polycondensation method to control the glass transition temperature to a moderate range.
It achieves high refractive index, low birefractive index, moderate glass transition temperature and high hydrophobicity, and meets the use requirements of optical lenses and optical films.
Smart Images

Figure BDA0005225930860000021 
Figure BDA0005225930860000022 
Figure BDA0005225930860000031
Abstract
Description
Technical Field
[0001] The present invention relates to the field of optical resins, and in particular to a thermoplastic resin composition for an optical forming body and application thereof. Background Art
[0002] Optical lens materials are very important for the optical systems of smartphones, drones, and smart driving. Compared with inorganic glass, organic resin materials have lower density and processing costs, and are suitable for large-scale production.
[0003] Examples of optical lens resin materials include polycarbonate, polymethyl methacrylate, and cycloolefin polymers, etc. Among them, polycarbonate resin has high transparency and excellent heat resistance, and thus has a wider application prospect.
[0004] However, the polycarbonate resin formed by bisphenol A has the disadvantages of large birefringence and low refractive index, and its application range is greatly limited. US4810771 proposes a polycarbonate resin prepared by using 9,9-bis-(4-hydroxyphenyl)fluorene as a monomer, which has low birefringence, but the refractive index is about 1.64, which cannot meet the application requirements of high-end optical systems. In order to further improve the refractive index of polycarbonate resin, it can be achieved by introducing more aromatic groups into the monomer. For example, WO2019044214 greatly improves the refractive index of polycarbonate resin by introducing 1-naphthyl and 2-naphthyl into monomers with a fluorene skeleton. Similarly, WO2019044875 introduces naphthalene, phenanthrene, dibenzofuran and other groups into monomers with a binaphthyl skeleton to improve the refractive index of polycarbonate resin. However, the aromatic groups introduced in the above patents are all benzene derivatives. Although they can effectively increase the refractive index of the material, they will also cause the glass transition temperature to be excessively increased. For example, the glass transition temperature of the homopolymer obtained based on 2,2-bis-(2-hydroxyethoxy)-1,1-binaphthyl in WO2019044875 is 115°C, while the glass transition temperature of the homopolymer obtained based on 2,2-bis-(2-hydroxyethoxy)-6,6-diphenyl-1,1-binaphthyl rises to 162°C. Too high a glass transition temperature will cause the resin to decompose or yellow during injection molding. In order to meet downstream processing requirements and product performance, the glass transition temperature of the resin should be controlled within 160°C. Therefore, how to suppress the excessive increase in the glass transition temperature while increasing the refractive index is a key issue that needs to be solved urgently.
[0005] In addition, in downstream applications, resin lenses need to be hydrophobic so that water droplets are not easily attached to the lens surface to ensure the clarity of the lens. The water contact angle is usually used to measure the hydrophobicity of the material. When the water contact angle is greater than 90°, the material is considered to be hydrophobic.
[0006] In summary, developing a thermoplastic resin composition with higher refractive index, moderate glass transition temperature, high hydrophobicity and industrial prospects is one of the research focuses in this field. Summary of the invention
[0007] The object of the present invention is to provide a thermoplastic resin composition, a method for preparing the same and its application in the field of optical formations. The thermoplastic resin composition has a high refractive index, low birefringence, a moderate glass transition temperature and high hydrophobicity, and can meet the requirements for use of optical lenses and optical films.
[0008] To achieve the above object, the present invention provides a thermoplastic resin composition.
[0009] A thermoplastic resin composition comprising a structural unit derived from a compound represented by general formula (A), a structural unit derived from a compound represented by general formula (B), and a structural unit derived from a compound represented by general formula (C),
[0010]
[0011] In the general formula (A), X represents an alkylene group having 1 to 4 carbon atoms, a and b each independently represent an integer of 1 to 10; R1 to R6 each independently represent a hydrogen atom, a halogen atom, a cyano group, an alkyl group having 1 to 20 carbon atoms, an alkoxy group having 1 to 20 carbon atoms, a cycloalkyl group having 5 to 20 carbon atoms, a cycloalkoxy group having 5 to 20 carbon atoms, an aryl group having 6 to 20 carbon atoms, or an aryloxy group having 6 to 20 carbon atoms,
[0012]
[0013] In the general formula (B), Y represents an alkylene group having 1 to 4 carbon atoms, c and d each independently represent an integer of 1 to 10; R7 to R 10 each independently represents a hydrogen atom, a halogen atom, a cyano group, an alkyl group having 1 to 20 carbon atoms, an alkoxy group having 1 to 20 carbon atoms, a cycloalkyl group having 5 to 20 carbon atoms, a cycloalkoxy group having 5 to 20 carbon atoms, an aryl group having 6 to 20 carbon atoms, or an aryloxy group having 6 to 20 carbon atoms,
[0014]
[0015] In the general formula (C), Z represents an alkylene group having 1 to 4 carbon atoms, e and f each independently represent an integer of 1 to 10; R 11 ~R 14Each independently represents a hydrogen atom, a halogen atom, a cyano group, an alkyl group having 1 to 20 carbon atoms, an alkoxy group having 1 to 20 carbon atoms, a cycloalkyl group having 5 to 20 carbon atoms, a cycloalkyloxy group having 5 to 20 carbon atoms, an aryl group having 6 to 20 carbon atoms, or an aryloxy group having 6 to 20 carbon atoms; M represents a direct bond, -O-, -S-, -NH-, a sulfone group or a sulfoxide group, an alkylene group having 1 to 6 carbon atoms, or a cycloalkylene group having 5 to 20 carbon atoms.
[0016] In one embodiment of the present invention, the proportion of the structural unit represented by the general formula (A) is 1 to 95 mol%,
[0017] The ratio of the structural unit represented by the general formula (B) is 2 to 90 mol%.
[0018] The proportion of the structural unit represented by the general formula (C) is 3 to 90 mol%;
[0019] Preferably,
[0020] The ratio of the structural unit represented by the general formula (A) is 5 to 80 mol%.
[0021] The ratio of the structural unit represented by the general formula (B) is 10 to 45 mol%,
[0022] The ratio of the structural unit represented by the general formula (C) is 10 to 55 mol%.
[0023] Another object of the present invention is to provide another thermoplastic resin composition.
[0024] A thermoplastic resin composition comprising a structural unit derived from a compound represented by the general formula (A) and a structural unit derived from a compound represented by the general formula (C),
[0025]
[0026] In the general formula (A), X represents an alkylene group having 1 to 4 carbon atoms, a and b each independently represent an integer of 1 to 10; R1 to R6 each independently represent a hydrogen atom, a halogen atom, a cyano group, an alkyl group having 1 to 20 carbon atoms, an alkoxy group having 1 to 20 carbon atoms, a cycloalkyl group having 5 to 20 carbon atoms, a cycloalkoxy group having 5 to 20 carbon atoms, an aryl group having 6 to 20 carbon atoms, or an aryloxy group having 6 to 20 carbon atoms,
[0027]
[0028] In the general formula (C), Z represents an alkylene group having 1 to 4 carbon atoms, e and f each independently represent an integer of 1 to 10; R 11 ~R 14Each independently represents a hydrogen atom, a halogen atom, a cyano group, an alkyl group having 1 to 20 carbon atoms, an alkoxy group having 1 to 20 carbon atoms, a cycloalkyl group having 5 to 20 carbon atoms, a cycloalkyloxy group having 5 to 20 carbon atoms, an aryl group having 6 to 20 carbon atoms, or an aryloxy group having 6 to 20 carbon atoms; M represents a direct bond, -O-, -S-, -NH-, a sulfone group or a sulfoxide group, an alkylene group having 1 to 6 carbon atoms, or a cycloalkylene group having 5 to 20 carbon atoms.
[0029] In one embodiment of the present invention, the proportion of the structural unit represented by the general formula (A) is 1 to 95 mol%,
[0030] The proportion of the structural unit represented by the general formula (C) is 5 to 99 mol%;
[0031] Preferably,
[0032] The ratio of the structural unit represented by the general formula (A) is 25 to 70 mol%.
[0033] The ratio of the structural unit represented by the general formula (C) is 30 to 75 mol%.
[0034] There is no particular limitation on the form in which the structural units derived from the compounds represented by the general formula (A), the general formula (B) and the general formula (C) described in the present invention are contained in the resin. For example, in the present invention, the thermoplastic resin composition may contain a copolymer containing structural units derived from the compounds represented by the general formula (A), the general formula (B) and the general formula (C), or may be a binary resin composition containing homopolymers composed of the respective structural units; or may be a blend obtained by blending a homopolymer containing structural units derived from the compound represented by the general formula (A) with a homopolymer containing structural units derived from the compound represented by the general formula (B) and with a homopolymer containing structural units derived from the compound represented by the general formula (C), or a blend obtained by blending a homopolymer containing structural units derived from the compound represented by the general formula (A) with a copolymer containing structural units derived from the compound represented by the general formula (B).
[0035] The thermoplastic resin composition of the present invention may include any structure of random, block and alternating copolymerization structures.
[0036] The thermoplastic resin composition of the present invention may contain auxiliary agents such as mold release agent, ultraviolet absorber, fluidity improver, crystal nucleating agent, reinforcing agent, dye, antistatic agent or antibacterial agent. As is well known in the art, the above auxiliary agents and their contents are well known to those skilled in the art.
[0037] The thermoplastic resin composition of the present invention can be prepared by reacting dihydroxy compounds represented by general formula (A), general formula (B) and general formula (C) with carbonic acid diester and / or dicarboxylic acid and / or dicarboxylic acid ester.
[0038] Preferably, the dihydroxy compound is produced by reacting with a carbonic acid diester and / or a dicarboxylic acid and / or a dicarboxylic acid ester in the presence of a basic compound catalyst, an ester exchange catalyst or a mixed catalyst consisting of both, or in the absence of a catalyst, by a melt transesterification polycondensation method.
[0039] Preferably, the dihydroxy compound represented by general formula (A) is at least one of the following structures:
[0040]
[0041] Preferably, the dihydroxy compound represented by general formula (B) is at least one of the following structures:
[0042]
[0043] Preferably, the dihydroxy compound represented by general formula (C) is at least one of the following structures:
[0044]
[0045] In the present invention, the carbonic acid diester is one or more of diphenyl carbonate, ditolyl carbonate, diethylphenyl carbonate, diisopropylphenyl carbonate, dimethyl carbonate, diethyl carbonate, dibutyl carbonate, and dicyclohexyl carbonate, preferably diphenyl carbonate;
[0046] The dicarboxylic acid is any one of terephthalic acid, terephthalic acid, 1,4-naphthalene dicarboxylic acid, 2,6-naphthalene dicarboxylic acid, 2,2-biphenyl dicarboxylic acid, 1,4-cyclohexane dicarboxylic acid, and 2,2'-bis(carboxymethoxy)-1,1'-binaphthyl, or a combination of at least two thereof, preferably terephthalic acid and / or 2,6-naphthalene dicarboxylic acid;
[0047] The dicarboxylic acid ester is any one of dimethyl terephthalate, diethyl terephthalate, dimethyl terephthalate, dimethyl 1,4-naphthalene dicarboxylate, dimethyl 2,6-naphthalene dicarboxylate, dimethyl 2,2-biphenyl dicarboxylate, dimethyl 1,4-cyclohexane dicarboxylate, and 2,2'-bis(carboxylic acid methyl ester methoxy)-1,1'-binaphthyl, or a combination of at least two thereof, preferably dimethyl terephthalate and / or dimethyl 2,6-naphthalene dicarboxylate.
[0048] In one embodiment of the present invention, the thermoplastic resin is one or more of polyester, polycarbonate, polyester carbonate, polyurethane, polysulfone, polyether, polyphenylene ether, polyurethane, polymethyl methacrylate, preferably one or more of polyester, polycarbonate and polyester carbonate.
[0049] In one embodiment of the present invention, the preparation method of polyester, polycarbonate and polyester carbonate comprises: subjecting a dihydroxy compound represented by the general structural formula (A), an optional dihydroxy compound represented by the general structural formula (B), an optional dihydroxy compound represented by the general structural formula (C) to transesterification or esterification condensation with a carbonic acid diester and / or a dicarboxylic acid and / or a dicarboxylic ester; preferably, the molar ratio of the carbonic acid diester and / or the dicarboxylic acid and / or the dicarboxylic ester to the sum of the added dihydroxy compounds of the general formulas (A), (B) and (C) is 1.0 to 1.12:1.
[0050] The alkaline compound catalyst of the present invention is one or more of lithium chloride, sodium chloride, potassium chloride, cesium chloride, lanthanum acetylacetonate, cerium acetylacetonate, sodium hydroxide, magnesium hydroxide, calcium hydroxide, strontium hydroxide, barium hydroxide, lithium bicarbonate, sodium bicarbonate, potassium bicarbonate, magnesium bicarbonate, calcium bicarbonate, strontium bicarbonate, barium bicarbonate, sodium carbonate, magnesium carbonate, calcium carbonate, strontium carbonate, barium carbonate, magnesium acetate, calcium acetate, strontium acetate, barium acetate, magnesium stearate, calcium stearate, calcium benzoate, phenyl magnesium phosphate, tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrapropylammonium hydroxide, tetrabutylammonium hydroxide, trimethylbenzylammonium hydroxide, triethylamine, dimethylbenzylamine, triphenylamine, diethylamine, tetramethylammonium borohydride, tetrabutylammonium borohydride, tetrabutylammonium tetraphenylborate, and tetraphenylammonium tetraphenylborate, preferably one or more of sodium hydroxide, sodium bicarbonate, and cesium carbonate.
[0051] The transesterification catalyst of the present invention can use one or more of zinc acetate, zinc benzoate, zinc 2-ethylhexanoate, tin chloride, tin acetate, cerium acetylacetonate, zirconium acetylacetonate, zirconium acetate, and tetrabutoxyzirconium, preferably one or more of lanthanum acetylacetonate, zirconium acetate, and zinc acetate.
[0052] The molar ratio of the sum of the basic compound catalyst and / or the transesterification catalyst to the sum of the dihydroxy compounds is 1×10 -8 ~5×10 -4 , the preferred ratio is 1×10 -6 ~2×10 -4 .
[0053] In some preferred embodiments of the present invention, the preparation method of the thermoplastic resin composition comprises: adding the dihydroxy compound represented by the general formula (A), the optional general formula (B) and the general formula (C), the carbonic acid diester and / or the dicarboxylic acid and / or the dicarboxylic acid ester, the catalyst, and the optional auxiliary agent into the reactor, fully replacing the air in the reactor with nitrogen for 3 to 5 times, and then heating the reactor to melt the material, the melting temperature is 180 to 210°C, preferably 190 to 200°C, and the residence time of this stage is 40 to 100 minutes, preferably 50 to 80 minutes. After the material is melted, stirring is started, the pressure reduction or pressure increase control is turned on, and the temperature is raised to the transesterification reaction temperature, the transesterification reaction temperature is 210 to 250°C, preferably 220 to 240°C, and the residence time of this stage is 60 to 320 minutes, preferably 150 to 240 minutes. Then, the pressure is further reduced and the temperature is increased to start the polycondensation reaction. The system pressure at this stage is 10-500 Pa (A), preferably 50-100 Pa (A), the reaction temperature at this stage is 230-270° C., preferably 230-255° C., and the residence time at this stage is 10-120 min, preferably 20-60 min. During the reaction, the generated small molecular compounds are immediately removed by distillation, and a high molecular weight thermoplastic resin composition is finally obtained in the reactor.
[0054] The blend of the present invention can be obtained by blending different thermoplastic resin compositions obtained by polymerization in an extruder, a kneader, a mixer and the like.
[0055] In one embodiment of the present invention, the water contact angle of the composition is 90° to 120°, preferably 100° to 110°, as tested according to the method specified in the national standard GB / T 30693-2014.
[0056] In one embodiment of the present invention, the weight average molecular weight Mw of the composition is 10,000 to 180,000, preferably 30,000 to 80,000.
[0057] Another object of the present invention is to provide an application of the thermoplastic resin composition.
[0058] An application of the thermoplastic resin composition is to use the thermoplastic resin composition for an optical formed body, preferably an optical lens and an optical film.
[0059] Another object of the present invention is to provide an optical lens.
[0060] An optical lens adopts the above-mentioned thermoplastic resin composition.
[0061] Another object of the present invention is to provide an optical film.
[0062] An optical film, wherein the lens adopts the above-mentioned thermoplastic resin composition.
[0063] In the present invention, the compound shown in the general formula (A) contains an azulene structure, which has a high polarizability and is conducive to inducing the close stacking of molecular chains, so a higher refractive index can be achieved. In addition, since the rigidity of the azulene structure is weaker than that of structures such as phenanthrene, the glass transition temperature of the resin composition will not rise very high. In terms of solubility, the combination of the five-membered ring and the seven-membered ring in the azulene structure makes the non-polarity of its molecule stronger than that of symmetrical aromatic structures such as naphthalene, thereby improving the hydrophobicity of the resin composition.
[0064] Compared with the prior art, the beneficial effects of the present invention are:
[0065] The thermoplastic resin composition of the present invention has a high refractive index, a moderate glass transition temperature, is easy to process, has good thermal properties, and is highly transparent, and can be used in the field of optical lenses. The optical lenses using the thermoplastic resin composition of the present invention can make the lenses lighter and thinner, reduce the weight of the lenses, and reduce the number of lenses, thereby reducing costs, and have broad application prospects.
[0066] The thermoplastic resin composition of the present invention has a refractive index nD of 1.66 to 1.72 at 20°C and a wavelength of 589 nm, an Abbe number of no more than 25, and an orientation birefringence Δn of 1.0×10 -3 Below, the glass transition temperature Tg is 120-145°C, and the water contact angle is greater than 90°;
[0067] The average transmittance of the thermoplastic resin composition at a wavelength of 780nm to 1000nm is above 87%. DETAILED DESCRIPTION
[0068] The present invention is now described as follows in conjunction with specific embodiments. It should be noted that the embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Any non-substantial improvements and adjustments made to the embodiments according to the content of the present invention are protected by the present invention.
[0069] 1) Weight average molecular weight (Mw): Gel permeation chromatography (GPC) was used with tetrahydrofuran as the developing solvent and a calibration curve was prepared using standard polystyrenes of known molecular weight (molecular weight distribution = 1). Based on this calibration curve, Mw was calculated from the retention time of GPC.
[0070] 2) Refractive index (nD): For a 1 mm thick film composed of the thermoplastic resin composition prepared in the example, the refractive index (nD) of the thermoplastic resin composition of the present invention at 20°C and a wavelength of 589 nm was measured using an Abbe refractometer according to the method of JIS-K-7142.
[0071] 3) Abbe number: The refractive index of a 0.1 mm thick film composed of the polycarbonate resin prepared in the example at wavelengths of 486 nm (F light), 589 nm (D light) and 656 nm (C light) at 20° C. was measured using an Abbe refractometer, and the Abbe number ν was calculated using the following formula:
[0072] ν=(nD-1) / (nF-nC).
[0073] 4) Orientation birefringence (Δn): After a cast film with a thickness of 0.1 mm was cut into 5.0 cm squares, both ends of the film were inserted into chucks (3.0 cm between chucks), and stretched to 1.5 times at Tg+5°C of the polycarbonate resin. The phase difference (Re) at 589 nm was measured using an ellipsometer, and the orientation birefringence (Δn) was calculated from the following formula.
[0074] Δn=Re / d
[0075] Δn: orientation birefringence; Re: phase difference; d: thickness.
[0076] 5) Glass transition temperature: measured using a differential scanning calorimeter (DSC) (measurement instrument: Hitachi High-Technologies Corporation (DSC7000X)).
[0077] 6) Light transmittance: The light transmittance was measured by the method of JIS-K-7361-1 using a turbidity meter on a 1 mm thick specimen made of the polycarbonate resin obtained in the example.
[0078] 7) Water contact angle: The water contact angle test was performed using the method specified in the national standard GB / T 30693-2014.
[0079] 8) Nuclear magnetic resonance test: The test was conducted using JNM-ECA500 (500MHz) manufactured by JEOL Ltd. The measurement mode was 1 H-NMR, the solvent is CDCl3 (deuterated chloroform).
[0080] The sources of some reagents and raw materials used in the examples and comparative examples of the present invention are as follows. The remaining reagents and raw materials are all commercially available products unless otherwise specified:
[0081] The purity and sources of the main commercially available raw materials are as follows:
[0082] name purity source 2-Hydroxyazulene 98% Inokay Anthrone 99.6% Maclean Toluene 99.8% Inokay Thioglycolic acid ≥97% Inokay Anhydrous methanol ≥99.9% Inokay Phenoxyethanol 98% Inokay 2-[(2-phenyl)phenoxy]ethanol 98% Inokay 1,1-Binaphthol 99% Inokay Ethylene glycol monotoluenesulfonate 98% Inokay Diphenyl carbonate 99% Maclean
[0083] A1 was prepared according to the following method:
[0084] Weigh 172.9g 2-hydroxyazulene and 97.1g anthrone into a three-necked flask, add 500mL toluene, and stir thoroughly until dissolved. Slowly drop a mixture of 0.92g concentrated sulfuric acid and 0.21g thioglycolic acid into the above solution, heat to 70°C and react for 3.5h. After the reaction is completed, cool to room temperature and add sodium hydroxide solution to neutralize the system to neutrality. Add 600mL anhydrous methanol, separate out the solid thoroughly, crush it, filter it, wash it with methanol and dry it to obtain the target product A1. The NMR results of the target product are as follows: 1H-NMR (500MHz, CDCl3) / δ×10-6: 9.45 (s, 2H), 8.31 (d, 4H), 7.90 (m, 2H), 7.55 (m, 2H), 7.38-7.28 (m, 8H), 7.12 (d, 4H).
[0085] A2 was prepared according to the following method:
[0086] Weigh 174g of intermediate A1 and 4.30g of potassium hydroxide into 500mL of diethylene glycol dimethyl ether, fill with 0.5MPa nitrogen for replacement three times, heat to 110°C, pass ethylene oxide gas, keep the molar ratio of ethylene oxide to intermediate B at 2.36:1, and react for 5h. After the reaction is completed, cool to room temperature, filter, wash with water, and dry to obtain A2. The NMR results of the target product are as follows: 1H-NMR (500MHz, CDCl3) δ / ×10 -6 :8.31(d,4H),7.90(m,2H),7.55(m,2H),7.38(m,4H),7.12(d,4H),4.90(m,2H),4.33(t,4H),3.69(t,4H).
[0087] B1 is prepared by referring to the method disclosed in Example 1 of Patent CN112142574A. Specifically, 9-fluorenone is reacted with phenoxyethanol in the presence of a strong acid catalyst and a mercapto compound co-catalyst.
[0088] B2 is prepared by referring to the method disclosed in Example 1 of Patent CN112441889A. Specifically, it can be prepared by reacting 9-fluorenone with 2-[(2-phenyl)phenoxy]ethanol in the presence of a thiol-containing compound and an alkyl sulfonic acid.
[0089] C1 was prepared according to the method disclosed in patent RO105571B1.
[0090] C2 is prepared by referring to the methods disclosed in Japanese Patent Laid-Open No. 2014-227387, Japanese Patent Laid-Open No. 2014-227388 and Japanese Patent Laid-Open No. 2015-168658, including (1) a method of reacting 1,1-binaphthol with ethylene glycol monotoluenesulfonate, (2) a method of reacting binaphthols with halogenated alkanols or alkylene carbonates, and (3) a method of reacting 1,1-binaphthol with ethylene carbonate or propylene carbonate.
[0091] (9,9-bis(4-(2-hydroxyethoxy)phenyl)-2,7-di(2-naphthyl)fluorene and 9,9-bis[4-(2-hydroxyethoxy)phenyl]-2,7-diphenylfluorene can be prepared by referring to the methods disclosed in Reference Example 5 and Reference Example 1 of Patent CN 110741030 A, respectively.
[0092] Example 1
[0093] 51.17 g (0.095 mol) of A2, 1.87 g (0.005 mol) of C2, 23.56 g (0.11 mol) of diphenyl carbonate, 3.258 μg (1.0×10 -8 mol) cesium carbonate was placed in a 200ml four-necked flask with a stirrer and a distillation device, replaced with nitrogen 4 times, heated to 190°C under a nitrogen atmosphere of 101Kpa (A), and confirmed that the raw material was completely dissolved after 60 minutes of heating. Then, stirring was turned on, and the pressure was adjusted to 26Kpa (A). At the same time, the temperature was raised to 230°C at a rate of 30°C / hr. At this time, it was confirmed that phenol generated as a by-product began to distill out, and the reaction was maintained at 230°C for 180 minutes, and then the temperature was raised to 250°C at a rate of 60°C / hr. After the temperature reached 250°C, the pressure was gradually reduced to 50Pa (A) within 1 hour. The reaction was stirred under this condition for 60 minutes to terminate the reaction. After the reaction was completed, nitrogen was filled into the four-necked flask to restore it to normal pressure, and the generated thermoplastic resin composition was taken out, pelletized and formed, and the performance was evaluated. The results are listed in Table 1.
[0094] Example 2
[0095] 2.69 g (0.005 mol) of A2, 35.57 g (0.095 mol) of C2, 23.56 g (0.11 mol) of diphenyl carbonate, 3.258 μg (1.0×10 -8 mol) of cesium carbonate was placed in a 200 ml four-necked flask with a stirrer and a distillation apparatus. Otherwise, the same operation as in Example 1 was carried out. The results are listed in Table 1.
[0096] Example 3
[0097] 26.93 g (0.05 mol) of A2, 18.72 g (0.05 mol) of C2, 22.28 g (0.104 mol) of diphenyl carbonate, 84.01 μg (1.0×10 -6 mol) sodium bicarbonate was placed in a 200ml four-necked flask with a stirrer and a distillation apparatus. Otherwise, the same operations as in Example 1 were performed. The results are listed in Table 1.
[0098] Example 4
[0099] 22.53 g (0.05 mol) of A1, 18.72 g (0.05 mol) of C2, 22.28 g (0.104 mol) of diphenyl carbonate, 84.01 μg (1.0×10 -6 mol) sodium bicarbonate was placed in a 200ml four-necked flask with a stirrer and a distillation apparatus. Otherwise, the same operations as in Example 1 were performed. The results are listed in Table 1.
[0100] Example 5
[0101] 2.69 g (0.005 mol) of A2, 53.16 g (0.09 mol) of B2, 1.87 g (0.005 mol) of C2, 21.64 g (0.101 mol) of diphenyl carbonate, 6.806 mg (2.0 × 10 -5 mol) of tetrabutyl titanate was placed in a 200 ml four-necked flask equipped with a stirrer and a distillation apparatus. Except for this, the same operation as in Example 1 was carried out. The results are listed in Table 1.
[0102] Example 6
[0103] 48.48 g (0.09 mol) of A2, 2.95 g (0.005 mol) of B2, 1.87 g (0.005 mol) of C2, 22.49 g (0.105 mol) of diphenyl carbonate, 13.08 μg (3.0×10 -8 mol) lanthanum acetylacetonate was placed in a 200 ml four-necked flask with a stirrer and a distillation apparatus. Otherwise, the same operation as in Example 1 was carried out. The results are listed in Table 1.
[0104] Example 7
[0105] 2.69 g (0.005 mol) of A2, 2.95 g (0.005 mol) of B2, 33.70 g (0.09 mol) of C2, 23.14 g (0.108 mol) of diphenyl carbonate, 6.806 mg (2.0 × 10 -5 mol) of tetrabutyl titanate was placed in a 200 ml four-necked flask equipped with a stirrer and a distillation apparatus. Except for this, the same operation as in Example 1 was carried out. The results are listed in Table 1.
[0106] Example 8
[0107] 21.55 g (0.04 mol) of A2, 17.72 g (0.03 mol) of B2, 11.23 g (0.03 mol) of C2, 22.71 g (0.106 mol) of diphenyl carbonate, 340.32 μg (1.0×10 -6 mol) of tetrabutyl titanate was placed in a 200 ml four-necked flask equipped with a stirrer and a distillation apparatus. Except for this, the same operation as in Example 1 was carried out. The results are listed in Table 1.
[0108] Example 9
[0109] 18.02 g (0.04 mol) of A2, 18.02 g (0.03 mol) of B1, 18.72 g (0.03 mol) of C1, 23.35 g (0.109 mol) of diphenyl carbonate, 9.18 μg (5.0×10 -8 mol) of zinc acetate was placed in a 200 ml four-necked flask equipped with a stirrer and a distillation apparatus. Otherwise, the same operation as in Example 1 was carried out. The results are listed in Table 1.
[0110] Comparative Example 1
[0111] Compared with Example 3, the only difference is that A2 is changed to (9,9-bis(4-(2-hydroxyethoxy)phenyl)-2,7-di(2-naphthyl)fluorene. Other than this, the same operation as Example 3 was carried out. The results are listed in Table 1.
[0112] Comparative Example 2
[0113] Compared with Example 4, the only difference is that A1 is changed to 9,9-bis[4-(2-hydroxyethoxy)phenyl]-2,7-diphenylfluorene. Other than this, the same operation as Example 4 was carried out, and the results are listed in Table 1.
[0114] Table 1
[0115]
[0116] Those skilled in the art will appreciate that, based on the teachings of this specification, some modifications or adjustments may be made to the present invention, and these modifications or adjustments should also be within the scope defined by the claims of the present invention.
Claims
1. A thermoplastic resin composition, characterized in that comprising a structural unit derived from a compound represented by the general formula (A), a structural unit derived from a compound represented by the general formula (B), and a structural unit derived from a compound represented by the general formula (C), In the general formula (A), X represents an alkylene group having 1 to 4 carbon atoms, a and b each independently represent an integer of 1 to 10; R1 to R6 each independently represent a hydrogen atom, a halogen atom, a cyano group, an alkyl group having 1 to 20 carbon atoms, an alkoxy group having 1 to 20 carbon atoms, a cycloalkyl group having 5 to 20 carbon atoms, a cycloalkoxy group having 5 to 20 carbon atoms, an aryl group having 6 to 20 carbon atoms, or an aryloxy group having 6 to 20 carbon atoms, In the general formula (B), Y represents an alkylene group having 1 to 4 carbon atoms, c and d each independently represent an integer of 1 to 10; R7 to R 10 each independently represents a hydrogen atom, a halogen atom, a cyano group, an alkyl group having 1 to 20 carbon atoms, an alkoxy group having 1 to 20 carbon atoms, a cycloalkyl group having 5 to 20 carbon atoms, a cycloalkoxy group having 5 to 20 carbon atoms, an aryl group having 6 to 20 carbon atoms, or an aryloxy group having 6 to 20 carbon atoms, In the general formula (C), Z represents an alkylene group having 1 to 4 carbon atoms, e and f each independently represent an integer of 1 to 10; R 11 ~R 14 Each independently represents a hydrogen atom, a halogen atom, a cyano group, an alkyl group having 1 to 20 carbon atoms, an alkoxy group having 1 to 20 carbon atoms, a cycloalkyl group having 5 to 20 carbon atoms, a cycloalkyloxy group having 5 to 20 carbon atoms, an aryl group having 6 to 20 carbon atoms, or an aryloxy group having 6 to 20 carbon atoms; M represents a direct bond, -O-, -S-, -NH-, a sulfone group or a sulfoxide group, an alkylene group having 1 to 6 carbon atoms, or a cycloalkylene group having 5 to 20 carbon atoms.
2. The thermoplastic resin composition according to claim 1, characterized in that in, The ratio of the structural unit represented by the general formula (A) is 1 to 95 mol%. The ratio of the structural unit represented by the general formula (B) is 2 to 90 mol%. The proportion of the structural unit represented by the general formula (C) is 3 to 90 mol%; Preferably, The ratio of the structural unit represented by the general formula (A) is 5 to 80 mol%. The ratio of the structural unit represented by the general formula (B) is 10 to 45 mol%, The ratio of the structural unit represented by the general formula (C) is 10 to 55 mol%.
3. A thermoplastic resin composition, characterized in that comprising a structural unit derived from a compound represented by the general formula (A) and a structural unit derived from a compound represented by the general formula (C), In the general formula (A), X represents an alkylene group having 1 to 4 carbon atoms, a and b each independently represent an integer of 1 to 10; R1 to R6 each independently represent a hydrogen atom, a halogen atom, a cyano group, an alkyl group having 1 to 20 carbon atoms, an alkoxy group having 1 to 20 carbon atoms, a cycloalkyl group having 5 to 20 carbon atoms, a cycloalkoxy group having 5 to 20 carbon atoms, an aryl group having 6 to 20 carbon atoms, or an aryloxy group having 6 to 20 carbon atoms, In the general formula (C), Z represents an alkylene group having 1 to 4 carbon atoms, e and f each independently represent an integer of 1 to 10; R 11 ~R 14 Each independently represents a hydrogen atom, a halogen atom, a cyano group, an alkyl group having 1 to 20 carbon atoms, an alkoxy group having 1 to 20 carbon atoms, a cycloalkyl group having 5 to 20 carbon atoms, a cycloalkyloxy group having 5 to 20 carbon atoms, an aryl group having 6 to 20 carbon atoms, or an aryloxy group having 6 to 20 carbon atoms; M represents a direct bond, -O-, -S-, -NH-, a sulfone group or a sulfoxide group, an alkylene group having 1 to 6 carbon atoms, or a cycloalkylene group having 5 to 20 carbon atoms.
4. The thermoplastic resin composition according to claim 3, characterized in that in, The ratio of the structural unit represented by the general formula (A) is 1 to 95 mol%. The proportion of the structural unit represented by the general formula (C) is 5 to 99 mol%; Preferably, The ratio of the structural unit represented by the general formula (A) is 25 to 70 mol%. The ratio of the structural unit represented by the general formula (C) is 30 to 75 mol%.
5. The thermoplastic resin composition according to any one of claims 1 to 4, characterized in that: The thermoplastic resin is one or more of polyester, polycarbonate, polyester carbonate, polyurethane, polysulfone, polyether, polyphenylene ether, polyurethane, polymethyl methacrylate, preferably one or more of polyester, polycarbonate and polyester carbonate.
6. The thermoplastic resin composition according to any one of claims 1 to 5, characterized in that: in, The preparation method of polyester, polycarbonate and polyester carbonate comprises: subjecting a dihydroxy compound represented by a general structural formula (A), an optional dihydroxy compound represented by a general structural formula (B), an optional dihydroxy compound represented by a general structural formula (C) to transesterification polycondensation or esterification polycondensation with a carbonic acid diester and / or a dicarboxylic acid and / or a dicarboxylic acid ester; Preferably, the molar ratio of carbonic acid diester and / or dicarboxylic acid and / or dicarboxylic acid ester to the sum of the added dihydroxy compounds of general formula (A), (B) and (C) is 1.0 to 1.12:
1.
7. The thermoplastic resin composition according to any one of claims 1 to 6, characterized in that: The water contact angle of the composition is 90° to 120°, preferably 100° to 110°; And / or, the weight average molecular weight Mw of the composition is 10,000 to 180,000, preferably 30,000 to 80,000.
8. Use of the thermoplastic resin composition according to any one of claims 1 to 7, wherein the thermoplastic resin composition is used for an optical formed body, preferably an optical lens and an optical film.
9. An optical lens, comprising the thermoplastic resin composition according to any one of claims 1 to 7.
10. An optical film, wherein the lens is made of the thermoplastic resin composition according to any one of claims 1 to 7.
Citation Information
Patent Citations
Synthesis method of 9, 9-di [4-(2-hydroxyethoxy) phenyl] fluorene
CN112142574A
Production method of binaphthalene compound
JP2014227387A
Production method of binaphthalene compound
JP2014227388A
Method for producing 2,2'-bis(2-hydroxyethoxy)-1,1'-bi-naphthalene
JP2015168658A
Preparation process for 2,2'-dihidroxi-1,1'-dinaphthylmethane derivates
RO105571B1